PERBEDAAN KUALITAS CITRA MRI LUMBAL SEKUEN TIWI TSE POTONGAN SAGITAL DENGAN DAN TANPA PENGGUNAAN SENSITIVITY ENCODING (SENSE) PADA KASUS HERNIA NUCLEUS PULPOSUS - Rini Indrati; Iin Saputri Sahlan; Bambang Satoto; Siti Daryati (Poltekkes Kemenkes Semarang, 2020)
Background: Parallel imaging is a time-reduction technique that uses phased-array coils. Phased array coils measure and process signals from a piece, then combine pieces to form an image of a larger area of anatomy. Commonly used imaging parallel technique is one of them is sensitivity encoding or SENSE. This research is the difference of image quality MRI Lumbal sequence T1WI TSE of sagittal pieces with and without the use of SENSE in the case of hernia nucleus pulposus (HNP). The aim of this research is to know the difference between SNR, anatomy information and better image quality and anatomical information. MRI Lumbal sequence T1WI TSE sagittal pieces with and without the SENSE in HNP.Methods: The type of this research is quantitative with an experimental approach, The research was conducted in RS dr. Saiful Anwar Malang. The research was taken from Lumbal MRI examination in 9 patients with predetermined exclusion and inclusion criteria of T1WI TSE sectional pieces with and without the use of SENSE in HNP. Image assessment was done by two radiologists. Analysis of data used paired T-test and Wilcoxon test with alpha 5%.Results: The results showed that there was a difference in image quality of MRI Lumbal T1WI TSE sequence of sagittal pieces with and without the use of SENSE in HNP with p-value = 0.001, and anatomic information with p-value = 0.001. Sensitivity encoding resulted in better image quality and anatomical information, with mean values at SNR 181,4333, and rank information anatomy 11,00.Conclusion: There is a difference in SNR and anatomical information between the use of SENSE andwithout the use of SENSE on sagittal lumbar MRI. The use of SENSE is capable of producing quality MRIimagery (SNR) and Anatomical Information on lumbar MRI lumbar sequences of sagittal slices.